Biotechnology on the farm and in the factory agrilcultural and industrial applications. - Sims, Tracey D; Films for the Humanities and Sciences (Hamilton , NJ : Films for the Humanities and Sciences, 2009)
A group of experts discuss the issues and challenges concerning the use of biotechnology in agriculture and industry in the twenty-first century. Topics include genetic engineering to increase crop yields; animal agriculture; and industrial applications of biotech in the manufacturing of chemicals, textiles, beverages, and fuel.
[j.1]. Bioinformatics, genomics, and proteomics: getting the big picture -- [j.2]. Biotechnology and your health: pharmaceutical applications -- [j.3]. Biotechnology on the farm and in the factory: agricultural and industrial applications -- [j.4]. The ethics of biotechnology.
Volume numbers assigned by cataloger in the order of the publisher's item numbers.
There are six chapter or topic includes in the video which are : introduction, agriculture: yesterday and today, genetics engeneering, animal agriculture, biotechnology and industry, summary and credits.
Director of photography/editor, Curt Massof.
Narrator: Gayle Friedman Gold.
DVD format.
Keywords: Agricultural biotechnology; Biotechnology